Sesamin Exerts Anti-Tumor Activity in Nasopharyngeal Carcinoma Through Inducing Autophagy and Reactive Oxygen Species Production - Deqiang An; Xianyao Jiang; Yucheng Yang (Frontiers in Bioscience-Landmark)
Background: Sesamin can suppress many cancers, but its effect on nasopharyngeal carcinoma (NPC) is unclear. Herein, we set out to pinpoint the possible changes in NPC due to Sesamin. Methods: The biological function of NPC cells exposed to Sesamin/N-acetyl-L-cysteine (NAC)/3-Methyladenine (3-MA) was detected, followed by evaluation of reactive oxygen species (ROS) production (dichlorodihydrofluorescein diacetate staining) and mitochondrial membrane potential (MMP) (flow cytometry). Proteins pertinent to apoptosis (cleaved caspase-3, cleaved poly (ADP-ribose) polymerase 1 (PARP1)), cell cycle (Cyclin B1), and autophagy (microtubule-associated protein light chain 3 (LC3)-I, LC3-II, Beclin-1, P62) were quantified by Western blot. After the xenografted tumor model in mice was established, the tumor volume and weight were recorded, and Ki-67 and cleaved caspase-3 levels were determined by immunohistochemical analysis. Results: Sesamin inhibited viability, proliferation, cell cycle progression and migration, induced apoptosis, increased ROS production, and decreased MMP in NPC cells. Sesamin elevated cleaved caspase-3/caspase-3, cleaved PARP1/PARP1, and Beclin-1 expressions as well as LC3-II/LC3-I ratio, while diminishing Cyclin B1 and P62 levels. NAC and 3-MA abrogated Sesamin-induced changes as above in NPC cells. Sesamin inhibited the increase of the xenografted tumor volume and weight, down-regulated Ki-67, and up-regulated cleaved caspase-3 in xenografted tumors. Conclusion: Sesamin exerts anti-tumor activity in NPC, as demonstrated by attenuated tumor proliferation and xenografted tumor volume and weight, as well as induced apoptosis in tumor tissues, consequent upon the promotion of autophagy and reactive oxygen species production.